Associations of vitamin D status with colorectal cancer risk and survival. Issue 3 (9th April 2021) - Zhou, Jian; Ge, Xianxiu; Fan, Xikang; Wang, Jiayu; Miao, Lin; Hang, Dong
Abstract: Biological evidence suggests that vitamin D has numerous anticancer functions, but the associations between vitamin D status and colorectal cancer (CRC) risk and survival remain inconclusive. Based on UK Biobank, we prospectively evaluated the associations of season‐standardized 25‐hydroxyvitamin D (25(OH)D) concentrations with CRC risk among 360 061 participants, and with survival among 2509 CRC cases. We observed an inverse linear relationship between 25(OH)D concentrations and CRC risk ( P for linearity = .01; HR per 1‐SD increment, 0.95; 95% CI, 0.91‐0.99). Compared to the lowest quartile of 25(OH)D, the highest quartile was associated with a 13% (HR, 0.87; 95% CI, 0.77‐0.98) lower risk of CRC. For CRC survival, compared to those in the lowest quartile of 25(OH)D, cases in the highest quartile had a 20% (HR, 0.80; 95% CI, 0.65‐0.99) lower risk for overall death. Our findings indicate that higher concentrations of serum 25(OH)D are associated with lower incidence and improved survival of CRC, suggesting a role of vitamin D in the pathogenesis of CRC. Abstract : What's new? Population‐based evidence remains inconclusive regarding associations between vitamin D status and colorectal cancer (CRC) risk and survival. Here, using data from the UK Biobank database, the authors prospectively evaluated potential links between CRC risk and season‐standardized 25‐hydroxyvitamin D concentrations. Analyses indicate that increased pre‐diagnostic concentrations of serum 25‐hydroxyvitamin D are associated with reduced CRC incidence, as well as with improved CRC survival. The findings suggest that vitamin D has a role in the pathogenesis of CRC, supporting future clinical trials to assess the effects of vitamin D supplementation on CRC risk and prognosis.